THE ONGOING "MYSTIC SYNTHESIS" - Musadad, Asep Nahrul (ALQALAM, 2015)
The rural Sundanese commonly recognize what so-called “pananyaan”, (literary means "who is asked or the place/someone to ask") as someone who has ability to reveal the world of unseen and give advices on all problem brought to him. In the more Islamic sense, he is also called “Ahli Hikmah”. The existence of “Pananyaan” has shown rhe presence of an acculturation. In which the mystic synthesis appeared between Islamic spearum and Sundanese local genius. The case of “pananyaan” within its depelovement is one of the keyword to trace that synthesis phase of mystic intersection. Start on preiminary sketch on “pananyaan” in Sundanese local custom, this paper aims to explore the acculturation domains in “pananyaan” after the emergence of lately established “ahli hikmah”. To do so, i examine three “pananyaan” from different generation, those who represented the different fashion in the ongoing depelovement. In this case, some of “pananyaan” rituals and their magical spells used by these elderly people had, in turn, reflected the traces of that mystic synthesis. Recently, the continuation of what had going on before. is still taking place until recent times in more puritanical direction. Keywords:  pananyaan, ahli hikmah, acculturation, mysticsynthesis